Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00391-014-0661-6
|View full text |Cite
|
Sign up to set email alerts
|

Kognitive Stimulation und Musikintervention bei stationär versorgten Menschen mit Demenz

Abstract: At least on a single-case approach, the study provides additional support for the potential of nonpharmacological interventions. Future studies should target logistical aspects in nursing homes, realistic planning of sample size, formulating adequate inclusion and exclusion criteria, and choosing suitable neuropsychological tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…[ 69 , 70 ] But quite a number of trails were restricted by appropriate endpoints, which resulted in this individually cognitive interventions lack of the relevant endpoints whose efficacy we must adopt to analysis. Therefore, from our conclusion above, PE, MT, CCT all have beneficial effects on older adults with AD and MCI, especially PE [ 58 , 71 ] and MT [ 72 , 73 ] as relatively obtained easily interventions. AD and MCI are progressive neurodegenerative disorders, and are still incurable.…”
Section: Discussionmentioning
confidence: 84%
“…[ 69 , 70 ] But quite a number of trails were restricted by appropriate endpoints, which resulted in this individually cognitive interventions lack of the relevant endpoints whose efficacy we must adopt to analysis. Therefore, from our conclusion above, PE, MT, CCT all have beneficial effects on older adults with AD and MCI, especially PE [ 58 , 71 ] and MT [ 72 , 73 ] as relatively obtained easily interventions. AD and MCI are progressive neurodegenerative disorders, and are still incurable.…”
Section: Discussionmentioning
confidence: 84%
“…Participants of the intervention group visited the multi-domain CST program NEUROvitalis senseful , specifically developed for AD dementia patients, based on the previously published standardized cognitive training program NEUROvitalis ( Baller et al, 2009 ). Liesk et al (2015) previously concluded that the original NEUROvitalis cognitive training program designed for healthy elderly and patients with MCI included parts, e.g., psychoeducational elements and training of cognitive strategies, that are too challenging for AD dementia patients. Accordingly, these demanding parts were removed for NEUROvitalis senseful while the group games remained in the modified version.…”
Section: Methodsmentioning
confidence: 99%
“…Körperliche Aktivität hingegen ist ein potenter Schutzfaktor, um das Morbiditäts-und Mortalitätsrisiko zu senken [4]. Niedrigschwellige aktivierende Bewegungsangebote, insbesondere in Verbindung mit Musik, wie die aktivierende Pflege, können die Agitiertheit bei Demenz als eine Ressource nutzen, um zu Bewegungsübungen zu motivieren und sind eine kostengünstige Alternative zur medikamentösen Sedierung bei Agitiertheit [5]. Aktivierende Pflege ist ein sektorenüberreifendes, interdisziplinäres Angebot von qualifizierten Pflegenden und Betreuungskräften, das bei den zu Pflegenden ressourcenorientiert die Alltagskompetenz fördert.…”
Section: Körperliche Aktivität Wirkt Präventivunclassified